Impact of Baseline Muscle Mass and Myosteatosis on the Development of Early Toxicity During First-Line Chemotherapy in Patients With Initially Metastatic Pancreatic Cancer - Hong, Sun; Kim, Kyung Won; Park, Hyo Jung; Ko, Yousun; Yoo, Changhoon; Park, Seo Young; Khang, Seungwoo; Jeong, Heeryeol; Lee, Jeongjin (Frontiers in Oncology, 2022)
Objectives: Chemotherapy is currently the only treatment option for metastatic pancreatic cancer (PDAC) but leads to frequent adverse events that impact quality of life and can cause treatment interruption. We evaluated the role of baseline CT-assessed body composition in predicting early toxicity during the first cycle of a first-line chemotherapy in patients with metastatic PDAC. Methods: This retrospective study included 636 patients with initially metastatic PDAC who underwent first-line chemotherapy between January 2009 and December 2019. The chemotherapy regimen, baseline laboratory data, and body composition parameters acquired from a baseline CT scan were obtained for these subjects. The skeletal muscle index (SMI) was used to detect sarcopenia, and myosteatosis was defined as a low-attenuated muscle area divided by skeletal muscle area (LAMA/SMA) ≥ 20%. Univariate and multivariable binary logistic regression analyses were performed using bootstrapping with 500 interactions to identify predictors of grade 3–4 toxicity, and any treatment-modifying toxicity which led to a dose reduction, delayed administration, and drug skipping or discontinuation. Results: During the first cycle of the first-line chemotherapy in the study cases, grade 3–4 and treatment-modifying toxicities occurred in 160 (25.2%) and in 247 (38.8%) patients, respectively. The presence of both sarcopenia and myosteatosis, but not sarcopenia alone, was significantly associated with the occurrence of both grade 3-4 (odd ratio [OR], 1.73; 95% confidence interval [CI], 1.14–2.63) and treatment-modifying (OR, 1.83; 95% CI, 1.26–2.66) toxicity. Conclusions: The presence of both sarcopenia and myosteatosis assessed on baseline CT may be predictive of early chemotherapy-related toxicity in patients with metastatic PDAC.